Port service quality in the supply chain management context - Koh, Xiao Le. (2012)
Ports play an integral role in the transportation of goods. However, the emergence of global supply chains has changed the traditional role that ports undertake. Today, ports are entities embedded in supply chains and competitiveness of ports is dependent on the value they generate for the entire supply chain. As customers increasingly seek value from service providers for low price but yet high quality services, there is a pressing need to define service quality for the port sector. However, there has been limited research conducted for this sector, taking into account the integration of ports in the supply chains.